Freedom of the Press In the Scope of Human Rights - Sri Ayu Astuti (Rechtsidee, 2014)
Freedom of expression and press freedom is the embodiment of the recognition of human rights. Freedom of expression is also the existence of press to disclose the news with honesty and do not get a pressure to deliver the news to the public space, which in news production is known as a work of journalism. Now the press has gained freedom of expression in the news production process which is guaranteed in the state constitution. Although Article 28 of the Constitution of the Republic of Indonesia 1945 does not point directly at the press, However, Article 28 F emphasis on processing and storage as well as ownership, excavations to information. It also contains provisions on the freedom of expression of others, which should be valued and respected. It shows equality for everyone in his position before the law in accordance with Article 27 1945 Constitution, which emphasizes the recognition of constitutional rights that belong to every person in the state of law in the Republic of Indonesia. Thus the press, which have freedom of expression in the writings of journalistic works are required to be responsible for the published news. So as not to face the legal issues and criminalization, then press should perform tasks and functions to enforce ethics as the precautionary principle when processing the news and broadcast it to the public space, as well as upholding human rights.